Penggunaan Metode Design Thinking Untuk Perancangan Ulang UI/UX Pada Aplikasi BCA Mobile - Putri Saidatuzzahra; Akhmad Rizal Dzikrillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Effective user interface (UI) and user experience (UX) design are essential in improving the convenience and efficiency of using digital applications. This study aims to redesign the UI/UX of the BCA Mobile application by applying the Design Thinking method to create a design that is more relevant to user needs. The research method begins with a literature study and data collection through the User Experience Questionnaire (UEQ) questionnaire filled out by 10 respondents to identify user problems and expectations. Furthermore, five stages of Design Thinking are applied, namely Empathize, Define, Ideate, Prototype, and Testing. The design prototype was retested with respondents using the UEQ questionnaire to evaluate aspects of attractiveness, efficiency, clarity, dependability, stimulation, and novelty. The results showed a significant increase in UEQ scores on all scales, with an average increase of 3.55 points from a range of ?3 to +3. This shows that the Design Thinking approach is able to produce a UI/UX design that is more responsive and in accordance with user expectations, as well as improving the quality of user interaction with the application. This research is expected to be a reference in the development of UI/UX for other digital banking applications.